Assessing the Knowledge, Attitude and Practices of Nurses in Implementing Infection Control Measures for Tuberculosis in Hospital: Literature Review - Alromimah, Mohammed Mutahar; Shanti Wardaningsih; Nur Chayati (Journal Of Nursing Practice, 2026)
Background: Tuberculosis (TB), caused by Mycobacterium tuberculosis, remains a major global health concern, particularly for healthcare workers (HCWs) who are at increased risk due to occupational exposure. This study evaluates nurses’ knowledge, attitudes, and practices (KAP) in implementing TB infection control measures in hospital settings across Ethiopia, Zimbabwe, Nepal, Saudi Arabia, India, Gabon, and Malaysia. Despite the availability of preventive measures, their inconsistent application due to inadequate training, resource shortages, and systemic challenges continues to hinder effective TB control. Identifying these gaps is crucial for improving infection prevention strategies. Purpose: This study aims to assess nurses' KAP regarding TB infection control, identify critical gaps in their understanding and practices, and highlight the need for targeted interventions such as in-service training, resource allocation, and stigma-reduction efforts. Methods: A literature review was conducted on studies published between 2020 and 2024 using the PubMed, ProQuest, and Scopus databases. The inclusion criteria focused on studies involving nurses in hospital settings that discussed knowledge, attitudes, and practices related to TB prevention. The 340 articles identified, 29 articles met the eligibility criteria after applying strict exclusion criteria for duplicate and non-empirical publications and studies that did not specifically focus on nurses in hospitals. To ensure accuracy and credibility, the included studies were assessed using the critical appraisal tool from the Joanna Briggs Institute (JBI) to minimize the risk of bias. Results: Findings revealed substantial gaps in nurses' knowledge and infection control practices, despite generally positive attitudes. For instance, many incorrectly relied on surgical masks instead of N95 respirators. Inconsistencies in infection control were linked to inadequate training, resource limitations, and high workloads. Conclusion: Addressing these deficiencies through structured training, improved resource distribution, and stigma-reduction strategies is essential to enhance TB prevention efforts in hospital settings.